The last mile(s) in modern input distribution: Evidence from northwestern Ethiopia - Minten, Bart; Koru, Bethlehem; Stifel, David (International Food Policy Research Institute, 2013)
Increasing adoption of modern inputs remains one of the best hopes toward higher agricultural production in developing coun-tries. Based on unique data from a quasi-experimental setting in northwestern Ethiopia, this study examines the “last mile(s)”—from the input distribution center to the farmer—in the chemical fertilizer and improved seed distribution system. We find that increasing transaction and transportation costs over a 35 kilometer distance contribute to a significant decline in incentives for modern input adoption and lead to a reduction to one quarter in modern input use. Farmers who live about 10 km from the distribution center face per unit transaction and transportation costs as high as the costs needed to bring the ferti-lizer from the international port to the input distribution center (about 1,000 km). Tackling the “last mile” costs should thus be a priority to improve modern input adoption in the country.